Chromatically unique 6-bridge graph theta(a,a,a,b,b,c) - N.S.A. Karim; Roslan Hasni; Gee-Choon Lau (Electronic Journal of Graph Theory and Applications (EJGTA), 2016)
For a graph $G$, let $P(G,λ)$ denote the chromatic polynomial of $G$. Two graphs $G$ and $H$ are chromatically equivalent if they share the same chromatic polynomial. A graph $G$ is chromatically unique if for any graph chromatically equivalent to $G$ is isomorphic to $G$. In this paper, the chromatically unique of a new family of 6-bridge graph $θ(a,a,a,b,b,c)$ where $2\le a\le b\le c$ is investigated.